Opportunistic Salpingectomy: A New Scope of Preventing a Deadly Disease (Delta Medical College Journal, 2024)
Background: Symptoms of ovarian cancer are non-specific and often do not arise until the cancer is in a late stage. Such late onset of symptoms and the lack of an effective screening test result in diagnosis at an advanced-stage for most patients of ovarian cancer. The fimbrial end of the fallopian tube has recently been suggested as the site of origin for epithelial ovarian cancers (EOC). Therefore, a change in practice with opportunistic salpingectomy (OS) at the time of hysterectomy has been advocated for prevention of ovarian cancer. Different gynaecological societies have published statements in favour of opportunistic salpingectomy in women at average population risk for ovarian cancer prevention. In recent years, salpingectomy has been increasingly performed for tubal sterilization also. We have gone through the available scientific publications and international guidelines in preparing this brief review in an attempt tobe familiar with the recent updated views regarding this issue.Delta Med Col J. Jan 2021;9(1):37-57